Inflammasome Meets Centrosome: Understanding the Emerging Role of Centrosome in Controlling Inflammasome Activation - Wu, Dandan; Zhang, Zhenzhen; Jiang, Xiaoli; Du, Yaning; Zhang, Shuangyan; Yang, Xiao-Dong (Frontiers in Immunology, 2022)
Inflammasomes are multi-protein platforms that are assembled in response to microbial and danger signals to activate proinflammatory caspase-1 for production of active form of IL-1β and induction of pyroptotic cell death. Where and how an inflammasome is assembled in cells has remained controversial. While the endoplasmic reticulum, mitochondria and Golgi apparatus have been reported to be associated with inflammasome assembly, none of these sites seems to match the morphology, number and size of activated inflammasomes that are microscopically observable as one single perinuclear micrometer-sized punctum in each cell. Recently, emerging evidence shows that NLRP3 and pyrin inflammasomes are assembled, activated and locally regulated at the centrosome, the major microtubule organizing center in mammalian cells, elegantly accounting for the singularity, size and perinuclear location of activated inflammasomes. These new exciting findings reveal the previously unappreciated importance of the centrosome in controlling inflammasome assembly and activation as well as inflammasome-related diseases.